Bibliometric Analysis of Five Major Colorectal Surgery Categories: Surpluses and Shortages. Issue 2 (12th January 2020) - Allar, Benjamin G.; Ore, Ana Sofia; Fabrizio, Anne C.; Messaris, Evangelos; Cataldo, Thomas E.
Abstract : Supplemental Digital Content is available in the text.